Control Strategy of Vinyl Chloride Production from Ethylene - A.S.Ahmed, Zeinab; Gasmelseed, Gurashi G. (Gezira Journal of Engineering and Applied Sciences; Vol 11 No 1 (2016), 2018)
The production of Vinyl Chloride (VC) from Ethylene dichloride (EDC) was investigated and the control strategy was developed, the process flow sheet consisted of two reactors one for the direct chlorination and the other for the oxychlorination process, furnace for thermal cracking and two separation columns. Each control loop was taken separately and its transfer function was developed. The characteristic equation was determined and used in Routh Array to determine the ultimate gain (Ku), and the ultimate period (Pu) was determined by direct substitution. Then the open loop transfer function for each loop was developed and used in Root locus and Bode plot using MATLAB format. The ultimate gains and period were used to get the average values which were introduced in Ziegler-Nichols table to get adjustable parameters. It is concluded that the manufacture of VC is important in the petrochemical industry and its quality need to be controlled. The reaction is exothermic and the temperature is controlled to the optimum temperature, this is introduced as the set point. The three methods of Routh, Root locus and Bode are identical and they are almost giving the same tuning parameters, however the average was taken to give more precise and correct results. The responses obtained simulate the system with (Rise time, Peak amplitude. Over shoot Settling time, Final value and Period of oscillation). Finally the system was checked for stability using the adjustable parameters obtained. All the systems were found to be stable, this is expected as the value of Kc was used after tuning.